HUBUNGAN PENDIDIKAN, PEKERJAAN DAN DUKUNGAN SUAMI TERHADAP KETERATURAN KUNJUNGAN ANC PADA IBU HAMILTRIMESTER III DI PUSKESMAS KEMAYORAN - Andini, Rima; Hasrida (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2025)
Efforts to accelerate the reduction of MMR are carried out by ensuring that every mother can access quality maternal health services, especially completing pregnancy checks (antenatal care/ ANC) from health workers. However, ANC coverage in several health centers is still not complete according to the target in each trimester. Various factors can influence the completeness of pregnant women in ANC. The aim of this research is to conduct an analysis of the relationship between education, working status and husband's support on the regularity of ANC visits for pregnant women in the third trimester. The design of this research is cross sectional. The location of this research was UPTD Kemayoran Community Health Center in December 2023. The sample used in this research was 30 pregnant women in the third trimester using accidental sampling. The independent variables are education, working status and husband's support. The dependent variable is the completeness of pregnancy checks/antenatal care (ANC). The bivariate analysis used in this research was the chi square test. Based on the results of the analysis, it is indicated that there is a relationship between education, working status, and husband's support on the regularity of ANC visits. The higher the mother's education, the more routine and complete her ANC visits are (p value 0.045). Mothers who do not work tend to make regular and complete ANC visits to check their pregnancy (p value 0.015). And mothers who receive support from their husbands tend to make regular and complete ANC visits to check their pregnancy (p value 0.001)